Investigación aplicada: creando cultura investigativa desde los programas académicos - Hernández-Belaides, Hernán José (Corporación Universitaria Americana, 2023)
In the era of information and knowledge, educational institutions must constantly evolve to prepare their students for the challenges and opportunities that arise in an ever-changing world. The American University Institution has stood out for its unwavering commitment to academic excellence and the integral formation of its students, and this book, "Applied Research: American University Institution's commitment to strengthen the research culture from the Academic Programs," produced by Professor Hernán Hernández Belaides, is a testimony of that commitment. Today it is clear to recognize that research is the engine that drives the advancement of knowledge, innovation and progress in society. In the academic context, Research Semilleros are vital spaces where students can enter the exciting world of inquiry, experimentation and discovery. These workshops not only foster critical thinking, problem solving and creativity, but also contribute significantly to students' professional training, preparing them to face the challenges of a competitive job market.